Strategies for the Prevention and Treatment of Surgical Site Infection in the Lumbar Spine. Issue 8 (October 2018) - Butler, Joseph S.; Wagner, Scott C.; Morrissey, Patrick B.; Kaye, Ian D.; Sebastian, Arjun S.; Schroeder, Gregory D.; Radcliff, Kristen; Vaccaro, Alexander R.
Abstract : Surgical site infection (SSI) following spine surgery can be devastating for both the patient and the surgeon. It leads to significant morbidity and associated health care costs, from readmissions, reoperations, and subsequent poor clinical outcomes. Complications associated with SSI following spine surgery include pseudarthrosis, neurological deterioration, sepsis, and death. Its management can be very challenging. The diagnosis of SSI involves the interpretation of combined clinical, laboratory, and occasionally radiologic findings. Most infections can be treated with an appropriate course of antibiotics and bracing if required. Surgical intervention is usually reserved for infections resistant to medical management, the need for open biopsy/culture, evolving spinal instability or deformity, and neurologic deficit or deterioration. A thorough knowledge of associated risk factors is required and patients should be stratified for risk preoperatively. The multifaceted approach of risk stratification, early diagnosis and effective treatment, is essential for successful prevention and effective treatment and crucial for a satisfactory outcome.